Obesity does not influence prostate intrafractional motion - Brown, Amy (J Med Radiat Sci, 2018)
INTRODUCTION: Motion of the prostate is problematic in the accurate delivery of external beam radiation therapy (EBRT) for prostate cancer. This study investigated the relationship between body mass index (BMI), an easily measured indicator of obesity, and prostate motion. METHODS: Prostate motion during EBRT was assessed by measuring the displacement of fiducial markers implanted within the prostate in 130 prostate cancer patients. Interfractional motion was corrected on daily imaging through pre‐treatment cone‐beam‐computed tomography (CBCT) and intrafractional motion measured using movie sequences captured using an electronic portal imaging device (EPID) during treatment delivery. RESULTS: There was no statistically significant relationship between the mean intrafractional motion and BMI, except in the left‐right (LR) translation (P = 0.049) over the study population. For each BMI category, there was no statistical significance (P > 0.05) between any of the translations/rotations except LR (P = 0.003). CONCLUSION: While intrafractional motion is an important consideration, prostate motion cannot be reliably predicted through measurement of patient's BMI.